Predição de ganho genético utilizando índices de seleção e reação à Dickeya zeae em genótipos de milho doce - Silva, Isadora Gonçalves da (2020)
The cultivation of sweet corn has expanded in Brazil, however, there are still restrictions on the availability of commercial hybrids and susceptibility to pathogens. Thus, it is necessary to select promising lines in the germplasm bank, considering the agronomic potential and resistance to diseases. The selection of superior genotypes can be carried out based on the selection indexes, allowing to obtain additional genetic gains for important characters. Therefore, the objectives of this work were to carry out the selection of sweet corn genotypes based on agronomic and organoleptic characters, using selection indexes and measuring the reaction of the most promising genotypes in Dickeya zeae. The work has been done in two steps. The field experiment was developed at the Experimental Vegetable Station at the Federal University of Uberlândia (UFU), Monte Carmelo Campus, in a randomized block design with 18 treatments (genotypes of F3 generation sweet corn) and three replications. Agronomic and organoleptic evaluations of sweet corn genotypes were performed. Statistical analysis was performed with the Genes program support. In this research, direct and indirect selection, index based on the sum of the ratings, index based on the desired gains and index based on the ideotype were used. The second step was carried out in a greenhouse at UFU, Umuarama Campus, where the reaction of eleven sweet corn accessions to two isolates of Dickeya zeae was evaluated. The experimental design was in randomized blocks, in a factorial scheme 11 x 2, with four replications. The treatments consisted of 10 genotypes of F3 generation sweet corn, belonging to the UFU Vegetable Germplasm Bank, Monte Carmelo Campus, (L2P1, L2P11, L2P33, L2P37, L2P45, L3P27, L4P19, L5P3, L5P18 and L5P42), and a hybrid of common commercial corn (AS1633) susceptible to bacteria that rots the stem, and two isolates of Dickeya zeae (UFU J23 and UFU H113). The bacterial suspension was inoculated 45 days after sowing and at 4, 8, 12 and 16 days after inoculation. The lesion length was measured to determine the incubation period, disease severity and area under the disease progress curve. Statistical analyzes were performed in the R and SigmaPlot programs. The method of direct and indirect selection was not satisfactory for the prediction of genetic gain in sweet corn. The sum of ratings index presented the highest total gain value and also provided a balanced distribution of selection gains, selecting the genotypes L2P1, L2P11, L2P37, L2P45 and L4P19, with superior performance for the character set. No genotype evaluated was resistant to Dickeya zeae. But, some were classified as moderately susceptible. However, the research can be carried out with other accesses from the UFU sweet corn germplasm bank.